IMPLEMENTASI PEMBELAJARAN SEJARAH DENGAN MENGINTEGRASIKAN NILAI-NILAI KEDIRGANTARAAN UNTUK MENINGKATKAN JATI DIRI BANGSA DAN PRESTASI SISWA KELAS XII IPS SMA NEGERI 1 MAOSPATI - Sulastri, Tutik; Mulyoto, M.; Sariyatun, S. (HISTORIKA, 2017)
The purpose of this research is (1). To find out the planning of learning history by integrating values in aerospace grade XII Social Science 1 Senior High School 1 Maospati, (2). To know the implementation of the learning history by integrating values in aerospace grade XII Social Science 1 Senior High School 1 Maospati, (3). To know sejauhmana the integration of values values aerospace aerospace with learning history can increase the nation identity and learning achievements of students in class XII Social Science 1 Senior High School 1 Maospati. This type of research is Research Action class, by using the method of learning the CTL (Contextual Teaching and Learning). The source population is students of class XII Social Science 1 Senior High School 1 Maospati. The technique of data collection by using the test, the interview, the now scale attitude, and a note field. The data analysis techniques using data reduction, the presentation of data, and the withdrawal of the conclusion. This research proves that the use of learning methods CTL against learners can enhance Identity Nations amounted to 91% and 90% of learning achievements. Implementation of a learning history by integrating aerospace values can increase the nation identity and learning achievements of students of class XII Social Science 1 Senior High School 1 Maospati.